(untitled) (Lafia Journal of Scientific and Industrial Research, 2024)
Malaria remains a serious public health concern in many nations, including Nigeria. The present study is a hospital based cross-sectional study and was aimed at determining the prevalence of malaria among patients in selected health centres in Otukpo, Benue State. Two hundred (200) samples were examined. Three millilitres (3mL) of venous blood was collected aseptically from each respondent and dispensed into an EDTA bottle. smears of the blood were made on grease-free clean slides and stained subsequently. The smears were examined under the microscope using X40 and X100 objective lenses for morphological features of Plasmodium spp. Statistical analysis was done using the statistical package for social sciences (SPSS) version 26. Person’s chi-square was used to determine association between variables at 95% confidence level. A p value less than or equal to 0.05 (p≤0.05) was considered to be indicative of a statistically significant relationship. Findings of the present study revealed a prevalence of 76.5% (n=153, N=200) for malaria parasites in the studied area. The prevalence of malaria parasite revealed a statistically significant difference with respect to location; St. Veronica’s clinic had the highest isolation rate (91.2%, n=31, p<0.05). The prevalence of malaria parasite (77.5%, n=69; p>0.05) showed female preponderance over male subjects. Patients >59 years (old adults) had the highest prevalence of malaria (100%, n=2; p>0.05). There is no statistically significant difference in the prevalence of malaria parasite with respect to gender and age. The high prevalence of malaria parasite in the study calls for concern.